Dose- and time-dependent effects of taxifolin on viability and mineralization markers of osteoblast-like cells - Loiane MASSUNARI; Rafaela Laruzo RABELO; Maria Luisa LEITE; Diana Gabriela SOARES; Giovana ANOVAZZI; Carlos Alberto Souza COSTA; Cristiane DUQUE (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The current study evaluated the effects of taxifolin treatments on the viability of osteoblast-like cells, and on the expression of early mineralization markers, as part of the ongoing search for new endodontic materials able to induce periapical healing without causing cytotoxicity. Saos-2 osteoblast-like cells were exposed to different concentrations of taxifolin (5 and 10 µM), applied as pretreatments either for 24h and 72h, or continuously throughout the experimental protocol. Cell viability using the methylthiazole tetrazolium (MTT) assay, alkaline phosphatase activity using thymolphthalein monophosphate assays, deposition of mineralized nodules using alizarin red staining, and expression of ALP and COL-1 by qPCR were determined after 6 and 13 days of treatment. The data were analyzed statistically (p<0.05). Taxifolin was not cytotoxic in the concentrations tested. Pretreatments with taxifolin for 24h and 72h at 10 µM stimulated ALP activity, and increased mineralized nodule deposition by Saos-2 cells. Continuous treatment with taxifolin was not effective in stimulating ALP activity and mineralization. ALP and COL-1 gene expression increased with taxifolin pretreatments, since the highest mRNA levels were observed after 72h of pretreatment with taxifolin at 10 µM on day 13. In conclusion, taxifolin was cytocompatible, and induced mineralization markers when applied for short periods in osteoblast-like cell culture.